You and your friend go to Tacos Galore for lunch. You order 3 soft tacos and 3 burritos at the total cost of $11.25. Your friend orders 4 soft tacos and 2 burritos at the cost of $10.00

Let t represent soft tacos, and B represent burritos. Make an equation for both orders, in any form.

7 answers

Let's define the variables:

  • Let \( t \) represent the cost of one soft taco.
  • Let \( b \) represent the cost of one burrito.

Based on your and your friend's orders, we can create the following equations:

  1. For your order (3 soft tacos and 3 burritos costing $11.25):

\[ 3t + 3b = 11.25 \]

  1. For your friend's order (4 soft tacos and 2 burritos costing $10.00):

\[ 4t + 2b = 10.00 \]

So, the equations for both orders are:

  1. \( 3t + 3b = 11.25 \)
  2. \( 4t + 2b = 10.00 \)
Given the equations, what would be the best method to solve for the cost of 1 taco and 1 burrito?

To solve for the cost of one soft taco (\( t \)) and one burrito (\( b \)), we can use either the substitution method or the elimination method. Here, I'll illustrate both methods, but the elimination method might be more straightforward in this case due to the coefficients.

Method 1: Elimination

We have the two equations:

  1. \( 3t + 3b = 11.25 \) (Equation 1)
  2. \( 4t + 2b = 10.00 \) (Equation 2)

To eliminate one of the variables, we can manipulate the equations. Let's first simplify Equation 1 by dividing everything by 3:

\[ t + b = \frac{11.25}{3} = 3.75 \] So, we rewrite Equation 1 as: \[ t + b = 3.75 \quad (Equation 3) \]

Next, we can manipulate Equation 2. To make the coefficients of \( b \) in both equations easy to eliminate, we can multiply Equation 3 by 2:

\[ 2t + 2b = 2 \cdot 3.75 = 7.50 \quad (Equation 4) \]

Now we have:

  • Equation 4: \( 2t + 2b = 7.50 \)
  • Equation 2: \( 4t + 2b = 10.00 \)

Next, we subtract Equation 4 from Equation 2:

\[ (4t + 2b) - (2t + 2b) = 10.00 - 7.50 \]

This simplifies to:

\[ 2t = 2.50 \]

Now, solving for \( t \):

\[ t = \frac{2.50}{2} = 1.25 \]

Now that we know \( t \), we can substitute back to find \( b \). Using Equation 3:

\[ 1.25 + b = 3.75 \]

Solving for \( b \):

\[ b = 3.75 - 1.25 = 2.50 \]

Thus, the costs are:

  • The cost of one soft taco \( t = 1.25 \)
  • The cost of one burrito \( b = 2.50 \)

Method 2: Substitution

If you prefer the substitution method, you could solve Equation 3 for \( b \):

\[ b = 3.75 - t \]

Substituting \( b \) into Equation 2:

\[ 4t + 2(3.75 - t) = 10.00 \]

Expanding and simplifying:

\[ 4t + 7.50 - 2t = 10.00 \ 2t + 7.50 = 10.00 \ 2t = 10.00 - 7.50 \ 2t = 2.50 \ t = 1.25 \]

Now using \( t = 1.25 \) in \( b = 3.75 - t \):

\[ b = 3.75 - 1.25 = 2.50 \]

In either method, we find that the cost of one soft taco is \( t = 1.25 \) and the cost of one burrito is \( b = 2.50 \).

Explain the elimination part in detail.

Certainly! Let's go through the elimination method step by step in detail for the problem involving the costs of soft tacos and burritos.

Step-by-Step Elimination Method

We started with our two equations:

  1. \( 3t + 3b = 11.25 \) (Equation 1)
  2. \( 4t + 2b = 10.00 \) (Equation 2)

Our goal is to eliminate one variable to solve for the other. We can do this by manipulating the equations in such a way that when we combine them, one of the variables cancels out.

Step 1: Simplify Equation 1

First, we simplify Equation 1. Since all terms can be divided by 3, we do this:

\[ 3t + 3b = 11.25 \]

Dividing the entire equation by 3 gives:

\[ t + b = \frac{11.25}{3} = 3.75 \]

Let's call this Equation 3:

  1. \( t + b = 3.75 \)

Step 2: Adjust Equation 3 for Elimination

Now, we want to manipulate Equation 3 to facilitate the elimination of the variable \( b \).

To do this, we can multiply Equation 3 by 2 so that the coefficient in front of \( b \) matches that in Equation 2 when we subtract:

\[ 2(t + b) = 2(3.75) \]

This yields:

\[ 2t + 2b = 7.50 \quad \text{(Equation 4)} \]

Step 3: Write the Two Equations for Elimination

Now we have:

  • Equation 4: \( 2t + 2b = 7.50 \)
  • Equation 2: \( 4t + 2b = 10.00 \)

Both equations have \( 2b \) on the left side. We are now ready to eliminate \( b \) by subtracting one equation from the other.

Step 4: Subtract Equation 4 from Equation 2

Now, we'll subtract Equation 4 from Equation 2:

\[ (4t + 2b) - (2t + 2b) = 10.00 - 7.50 \]

When we perform this subtraction, the \( 2b \) terms cancel out:

\[ 4t + 2b - 2t - 2b = 10.00 - 7.50 \]

This simplifies to:

\[ (4t - 2t) + (2b - 2b) = 2.50 \]

Which simplifies to:

\[ 2t = 2.50 \]

Step 5: Solve for \( t \)

Now we can solve for \( t \):

\[ t = \frac{2.50}{2} = 1.25 \]

Step 6: Substitute \( t \) back to find \( b \)

Now that we have \( t \), we can substitute it back into one of our earlier equations to find \( b \). We can use Equation 3:

\[ t + b = 3.75 \]

Substituting \( t = 1.25 \):

\[ 1.25 + b = 3.75 \]

Now solve for \( b \):

\[ b = 3.75 - 1.25 = 2.50 \]

Final Result

We now have the costs as follows:

  • Cost of one soft taco \( t = 1.25 \)
  • Cost of one burrito \( b = 2.50 \)

Summary of the Elimination Method

In summary, the elimination method involves:

  1. Simplifying one or both equations if possible.
  2. Manipulating the equations (by multiplication or division) to make the coefficients of one variable match.
  3. Subtracting one equation from the other to eliminate that variable.
  4. Solving for the remaining variable.
  5. Substituting back to find the initially eliminated variable.

This approach is efficient when the coefficients lend themselves to easy manipulation, as we showed in our example.

Now explain the substitution method.

Absolutely! Let’s go through the substitution method step-by-step in detail for the problem involving the costs of soft tacos and burritos.

Step-by-Step Substitution Method

As a reminder, we’re working with the same two equations:

  1. \( 3t + 3b = 11.25 \) (Equation 1)
  2. \( 4t + 2b = 10.00 \) (Equation 2)

Step 1: Solve One Equation for One Variable

We start by solving one of the equations for one variable. We can simplify Equation 1 first to make things easier.

Simplifying Equation 1:

We can divide everything in Equation 1 by 3:

\[ 3t + 3b = 11.25 \]

Divide by 3:

\[ t + b = \frac{11.25}{3} = 3.75 \]

Let’s call this Equation 3 for reference:

  1. \( t + b = 3.75 \)

Now, we can solve Equation 3 for \( b \):

\[ b = 3.75 - t \]

Step 2: Substitute for \( b \) in the Second Equation

Next, we substitute what we found for \( b \) into Equation 2:

\[ 4t + 2b = 10.00 \]

Substituting \( b = 3.75 - t \):

\[ 4t + 2(3.75 - t) = 10.00 \]

Step 3: Simplify and Solve for \( t \)

Now, we simplify the equation:

  1. Distributing the 2 in \( 2(3.75 - t) \):

\[ 4t + 7.50 - 2t = 10.00 \]

  1. Combine like terms (\( 4t - 2t \)):

\[ 2t + 7.50 = 10.00 \]

  1. Isolate \( t \) by subtracting 7.50 from both sides:

\[ 2t = 10.00 - 7.50 \]

This simplifies to:

\[ 2t = 2.50 \]

  1. Finally, divide by 2 to find \( t \):

\[ t = \frac{2.50}{2} = 1.25 \]

Step 4: Substitute \( t \) back to Find \( b \)

Now that we know the cost of one soft taco is \( t = 1.25 \), we can substitute this value back into our expression for \( b \) from Equation 3:

\[ b = 3.75 - t \]

Substituting \( t = 1.25 \):

\[ b = 3.75 - 1.25 \]

Thus:

\[ b = 2.50 \]

Final Result

We have determined the costs:

  • Cost of one soft taco \( t = 1.25 \)
  • Cost of one burrito \( b = 2.50 \)

Summary of the Substitution Method

In summary, the substitution method involves:

  1. Solving one of the equations for one variable.
  2. Substituting this expression into the other equation.
  3. Simplifying the resulting equation to isolate and solve for the first variable.
  4. Substituting the found value back into the first equation (or the rearranged equation) to find the value of the second variable.

This method is particularly useful when one equation is already easily solvable for one of the variables, as we demonstrated in this example.